(untitled) (Journal of the College of Education for Women, 2019)
The current search aims to identify First: To measure the level of authoritarian personality among the students of the sample as a whole. Second: Measurement of differences in the level of authoritarian personality among students in the middle school according to the following variables 0.Science (literary, scientific) 8. Sex (male - female) Third: the level of control site level among the students of the sample as a whole. Ra’aa: Measurement of differences in the level of the control site among junior students according to the following variables 0.Science (literary, scientific) 8. Sex (male - female) Fifth: Explain the relationship between the authoritarian personality and the locus of control among the students of the research sample. In order to achieve the objectives of the current research, the sample was randomized by the random method of 061 students from the middle school of the third directorate in accordance with the gender variables (male and female) and the academic and academic specialization (8105-8106) In order to measure the level of authoritarian personality in the students, the researcher built the measure of authoritarian personality, the number of paragraphs (51), after being presented to a committee of arbitrators and experts in this field, which is the apparent truth, extracted the strength of the standard of the scale paragraphs using the method of the two extremes and using the test of two independent samples, (1.15) except two paragraphs (2,82) were excluded from the scale because it is less than the level of significance required so that the number of paragraphs of the scale (42) (3) areas. After the calculation of the construction accuracy of the scale and the stability of the scale was calculated in the Vaccronbach method with a consistency coefficient (1.26). As for the measurement of the site of control, the researcher adopted the measure of sweetness 0121 (52), after it was modified. The necessary cytometric properties of the apparent honesty and the validity indicators of the structure of the two extremes were obtained and using Pearson correlation coefficient (2) were excluded because they were less than the required level of significance. If the scale became final (51), it was divided into (1) fields. The consistency of the scale was obtained by the Vaccronbach method with a consistency coefficient of 1.28. The researcher reached the following results: 0. The middle school students overcome them with a tolerant personality in their behavior. 8. There are no statistically significant differences in the authoritarian personality by gender. 3. There are no statistically significant differences for the authoritarian personality by variable (specialization). 4 - that the junior high school students in the direction of internal control and external in general. 5. There are statistically significant differences in the location of the locality according to the sex variable. The males tend to control their position internally. 6. There are no statistically significant differences in the location of the control by variable (specialization). 2. There is no statistically significant correlation between the authoritarian personality and the locus of control. In the light of the findings of the researcher, I made a number of conclusions, recommendations and suggestions mentioned in chapter .